An Indication of China's Policy towards Uighurs and its Implications by International Law Aspects - Mellisa Towadi; Nur Mohamad Kasim; Rumawi Rumawi; Siti Asifa Tahir (Universitas Negeri Gorontalo, 2021)
This article examines the Chinese government's policy towards Uighurs for the purpose of outlining and explaining indications of the policy that have implications on the legal aspects of this international law. This study was researched using normative juridical methods with expansive analysis based on logical-normative approaches. The results of the analysis show that broadly the policies China implements against the Uighur population are indicated to acts of discrimination. China's main interest is sovereignty, so of course, China will not allow the release of any territory from China. While the implications in the context of International Law as to uphold the guarantee of civil and political rights, liberal and democratic principles or independence, and individual freedom in relation to the state. The points of conflict identified, especially concerning the reach of equality of rights between ethnic Uighurs and other ethnicities in China, the prohibition of inhumane punishment and degrading dignity, and religious freedom.